Estudo de eventos de El Niño e La Niña em anéis de crescimento de árvores para a região Sul do Brasil - Lorensi, Caren (2012)
In climatology it is of fundamental importance to make predictions about the behavior of certain variables. For this it is necessary that current and past behavior of these variables is known. In this context, the use of natural records, such as the growth rings of trees, has become a very effective tool because it covers data of longer time scale. The dendroclimatologia is the study of climate through the analysis of growth rings of trees and it is based on the determination of climatic factors that are acting in the study area and thus causing variations in thickness of growth rings. In general, dendrochronology is a simple and inexpensive work, but highly effective. In the present work, it was developed a study of the climate through the growth rings of trees of the species Araucaria angustifolia which chronologies were obtained of samples collected from Concordia / SC, Passo Fundo / RS and São Francisco de Paula / RS. It was used a total of 34 samples, 08 samples from Concord, 12 samples from Passo Fundo and 14 samples from São Francisco de Paula/RS. The variations in thickness of growth rings were investigated considering the variable rainfall recorded in the localities of Passo Fundo and Caxias do Sul / RS. The time series of the Southern Oscillation Index (SOI) was also used in the study in order to know the influence of this phenomenon in the growth of trees. In the series of rings of tree growth it was applied a low-pass filter in order to remove long trends contained in this series. In the series of precipitation it was used a low-pass filter to period corresponding to SOI become evident. The method of Iterative Regression Analysis of Time Series (ARIST) was applied to the series in order to find common periods between growth rings and climate variables. The results showed that there is, in the time series of growth rings, signs similar to those found in the series of IOS with periods around 2 and 7 years. In the seasonal study, the results identified a trend of growing trees in the spring/summer.